Competencies Can Bridge the Interests of Business and Universities - Drummond, Don; Kachuck Rosenbluth, Ellen (Université d'Ottawa | University of Ottawa, 2015)
Universities have come under some criticism for not serving students and the business sector well in the school-to-work transition. Aggregate data show the transition is working reasonably well. Yet information that has recently become available points to ways in which the transition can be improved. Greater focus on general competencies may be the bridge that better links university, student and business interests. Business has identified such competencies as communication and problem solving as prime areas of interests in recruits. Some universities are broadening the scope of education from discipline-specific knowledge to encompass these competencies. While the approach has considerable intuitive appeal, mechanisms need to be put in place to track whether competency-based education enhances graduates' success in the workplace over time.
Keywords: Post-Secondary Education; school-to-work transition; skills; university; general competencies; economic growth